STRATEGI PENGEMBANGAN AGRIBISNIS TANAMAN KEDELAI DI DISTRIK SIDEY KABUPATEN MANOKWARI ( Soybean Agribusiness Development Strategy in Sidey, Manokwari District ) - Saut Simanungkalit (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2020)
The Agricultural sector plays an important role in the Indonesian economy. Agribusiness is a strategic step to increase the added value of agricultural resources through the use of technology, expand employment and increase community income. This study aims to identify internal factors (strengths and weakness) as well as eksternal factors (opportunities and threats) faced owned by soybean agribusiness in Manokwari Regency. For this reason, it is necessary to formulate a strategy than can be carried out in the development of soybean agribusiness in Manokwari Regency. Govermment strategies and policies must be directed towards improvement which is followed up thtroug the results of SWOT analysis that uses strategies S-O strengths to take advantage of opportunities, strategies of strength to avoid existing threats, strategies that take advantage of opportunities to overcome weakness and strategies to overcome weakness to avoid threats.